Spectral dependence of photoinduced optical effects in As40S60-xSex thin films - Voynarovych, Ivan; Bůžek, Jan; Pálka, Karel; Vlček, Miroslav (My University, 2016)
Spectral dependence of photoinduced structural transformation and related changes of Egopt, α and n of thermally evaporated ternary As40S60-xSex thin films have been studied under the exposure to bandgap and super-/subbandgap light of LED. The irradiation by bandgap and super-bandgap light with intensity 0.1 W/cm2 leads to partial photoinduced polymerization of molecular structural units into continuous network that is characteristic for the bulk glasses with appropriate stoichiometric composition. The efficiency of structural transformation depends on penetration depth of excitation beam. The maximum photosensitivity (i.e. changes of Egopt, α and n) were achieved at the wavelengths ~100 nm above the bandgap wavelength for each appropriate composition. Beyond the region of maximal photosensitivity the values of optical parameters and kinetics of photoinduced changes depend on relation between exposed and unexposed sublayer for super-bandgap beams or on absorption coefficient for sub-bandgap light.
Spektrální závislost fotoindukovaných jevů v tenkých vrstvách systému As40S60-xSex
Keywords: Ternary As–S–Se chalcogenide glasses; Thin films; Photoinduced effects; chalkogenidové sklo As-S-Se; tenké vrstvy; fotoindukované jevy